Building the Concept of Small and Medium Enterprise Business Resilience: Literature Review - Dinar Nur Affini; Veitzhal Rivai; Mafizatun Nurhayati; Dudi Permana; Ahmad H Sutawidjaya (Jurnal Manajemen dan Kewirausahaan, 2022)
Business resilience research has increased rapidly and received attention from researchers. However, the literature still provides few definitions, measurements, and variables that affect the concept. Therefore, there is still a gap in contributing the latest knowledge related to these fields and putting it in this journal article. On this occasion, researchers pay special attention to the resilience of SMEs in developing countries. The importance of SME business for the national economy so that it requires attention in resilience research. The researcher applies a well-structured systematic literature review procedure. This journal article offers (1) a review of the SME resilience literature from 2015 to November 2021, consisting of 72 articles, and (2) a review, specifically for developing countries. This review concludes that the definition of resilience varies widely, and its measurement and the factors that influence it vary widely. Not much resilience research has paid attention to the context of SMEs in developing countries. Based on the review results, researchers present features that can distinguish resilience; provide an alternative to add to the theoretical basis for research on resilience in the future.